Array based characterization of a terminal deletion involving chromosome subband 15q26.2: an emerging syndrome associated with growth retardation, cardiac defects and developmental delay - Björkhem Gudrun; Collin Anna; Davidsson Josef; Soller Maria (BMC, 2008)
Abstract Background Subtelomeric regions are gene rich and deletions in these chromosomal segments have been demonstrated to account for approximately 2.5% of patients displaying mental retardation with or without association of dysmorphic features. However, cases that report de novo terminal deletions on chromosome arm 15q are rare. Methods In this study we present the first example of a detailed molecular genetic mapping of a de novo deletion in involving 15q26.2-qter, caused by the formation of a dicentric chromosome 15, using metaphase FISH and tiling resolution (32 k) genome-wide array-based comparative genomic hybridization (CGH). Results After an initial characterization of the dicentric chromosome by metaphase FISH, array CGH analysis mapped the terminal deletion to encompass a 6.48 megabase (Mb) region, ranging from 93.86-100.34 Mb on chromosome 15. Conclusion In conclusion, we present an additional case to the growing family of reported cases with 15q26-deletion, thoroughly characterized at the molecular cytogenetic level. In the deleted regions, four candidate genes responsible for the phenotype of the patient could be delineated: IGFR1, MEF2A, CHSY1, and TM2D3. Further characterization of additional patients harboring similar 15q-aberrations might hopefully in the future lead to the description of a clear cut clinically recognizable syndrome.